Networked publics: multi-disciplinary perspectives on big policy issues - William H. Dutton (Internet Policy Review)
This special issue of Internet Policy Review is the first to bring together the best policy-oriented papers presented at the annual conference of the Association of Internet Researchers (AoIR). This issue is anchored in the 2017 conference in Tartu, Estonia, which was organised around the theme of networked publics. The seven papers span issues concerning whether and how technology and policy are reshaping access to information, perspectives on privacy and security online, and social and legal perspectives on informed consent of internet users. As explained in the editorial to this issue, taken together, the contributions to this issue reflect the rise of new policy, regulatory and governance issues around the internet and social media, an ascendance of disciplinary perspectives in what is arguably an interdisciplinary field, and the value that theoretical perspectives from cultural studies, law and the social sciences can bring to internet policy research.